Do conto ao encanto pela linha do trem: a valorização do patrimônio cultural local junto à educação infantil de Restinga Sêca – RS - Freitas, Ana Paula Porto de (2024)
The main objective of this dissertation is to stimulate heritage education in Early Childhood Education in the municipality of Restinga Sêca – RS, promoting the preservation of local cultural identity and is anchored in the assumptions of the UNESCO Quarta Colônia Mundial Geopark. We intend to arouse in Early Childhood Education children a taste for knowledge of local culture, using the Restinga Sêca Railway Station, which has a symbolic value for the municipality, as it was the driving force for its local development. In this way, we seek, in a playful way, to evoke children's knowledge about the history of the municipality, contributing to a greater understanding and appreciation of the local cultural heritage. We used the storytelling technique, followed by a drawing workshop to talk about the construction process of the building, the emancipation of the municipality, among others, to encourage children to learn about history and feel like they belong to the local community. To fulfill the intended purposes, a qualitative, bibliographic and exploratory research methodology was adopted. Qualitative research allowed exploring children's perceptions, emotions and experiences in relation to local cultural heritage, while bibliographic research provided theoretical basis to historically contextualize the subject “children” at the Railway Station and its relationship with the development of the municipality. Exploratory research made it possible to identify relevant information and discover new aspects of local history that could be shared in a playful way with children. In this way, the dissertation sought to promote a meaningful and pleasurable experience for children, encouraging learning in a creative and participatory way. This approach aroused children's interest in the history and cultural heritage of their community, contributing to the formation of citizens who are more aware and engaged in preserving the municipality's cultural identity. As a result, a book was created about the history of Restinga Sêca\RS, illustrated by the children, with an emphasis on the local Railway Station.